Characterization of the Full-Sized Pore Structure and Controlling Factors of the Coal-Bearing Shale in the Wuxiang Block, South-Central Qinshui Basin, China - Zhang, Xueqing; Li, Xianqing; Yang, Jingwei; Zhang, Boxiang; Sun, Jian; Yu, Zhenfeng (Frontiers in Earth Science, 2022)
The characterization of the full-sized pore structure is important for the evaluation and prediction of the reservoir of shale gas with strong heterogeneity. It is of great scientific significance to explore the pore structure characteristics of overmature coal-bearing shale. Core descriptions, X-ray diffraction (XRD), vitrinite reflectance (Ro), field emission scanning electron microscopy (FE-SEM), high-pressure mercury intrusion porosimetry (MIP), and low-pressure N2/CO2 gas adsorption (N2-/CO2-GA) experiments were performed on overmature coal-bearing shale samples from the Wuxiang block, south-central Qinshui Basin, China. The results show that the total organic carbon (TOC) ranged from 0.29 to 8.36%, with an average of 3.84%, and the organic matter (OM) is dominated by type III kerogen. The minerals in the shale primarily consist of clay (43–85.5%, averaging 52.1%) and quartz (12.6–61.2%, averaging 43.5%). The major clay minerals are illite-smectite (I/S) and illite, ranging from 22.5 to 55.6% (mean 41.4%) and 8.7–52.7% (mean 32%), respectively. FE-SEM images reveal that intraparticle pores (IntraP pores) and interparticle pores (InterP pores) are widely developed in clay minerals, and organic pores are occasionally present. Mesopores make the greatest contribution to the total pore volume (PV), and micropores are the major contributors to the specific surface area (SSA). Clays are the main controllers of micropore development. Mesopores developed in the clay mineral layers are promoted by I/S but inhibited by illite. Macropores and microfractures are mainly developed in clays and quartz and do not correlate significantly with the TOC, or mineral composition, due to the influence of compaction and cementation. The TOC and minerals affect pore structure characteristics mainly by influencing micropores.